2019
DOI: 10.1007/s10902-019-00123-9
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Daydreaming and Well-Being: Moderating Effects of Otaku Contents and Mindfulness

Abstract: The relationship between daydreaming and well-being were examined with mindfulness and consumption of Otaku contents (animations and games) as potential moderators. Recent theory suggests that both the context and contents of daydreaming matter in determining the beneficial effects of daydreaming. Mindfulness is a candidate for the former, whereas Otaku contents represent one for the latter. Metacognitive awareness and intentionality of daydreaming, and accepting relationship with the same, may facilitate such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…This negative association was observed for positive aspects of affective well-being (including positive affect; e.g., Crosswell et al, 2020; Miś & Kowalczyk, 2021, general well-being; e.g., Magan, 1985; Sugiura & Sugiura, 2020, and life satisfaction; Johannes et al, 2018; Mar et al, 2012) and negative aspects of affective well-being (including negative affect; Carciofo & Jiang, 2021; Franklin et al, 2013, depression; Seli et al, 2019, and anxiety; Kruger et al, 2020; Soffer-Dudek & Somer, 2018). Given evidence supporting the characterization of positive and negative affective measures as separate dimensions (Headey et al, 1984; Ryff et al, 2006), such distinction suggests that unprompted thought is implicated in changes in both dimensions of affective well-being.…”
Section: Discussionmentioning
confidence: 95%
“…This negative association was observed for positive aspects of affective well-being (including positive affect; e.g., Crosswell et al, 2020; Miś & Kowalczyk, 2021, general well-being; e.g., Magan, 1985; Sugiura & Sugiura, 2020, and life satisfaction; Johannes et al, 2018; Mar et al, 2012) and negative aspects of affective well-being (including negative affect; Carciofo & Jiang, 2021; Franklin et al, 2013, depression; Seli et al, 2019, and anxiety; Kruger et al, 2020; Soffer-Dudek & Somer, 2018). Given evidence supporting the characterization of positive and negative affective measures as separate dimensions (Headey et al, 1984; Ryff et al, 2006), such distinction suggests that unprompted thought is implicated in changes in both dimensions of affective well-being.…”
Section: Discussionmentioning
confidence: 95%
“…Others use daydreaming as an umbrella term for task-unrelated thought, which MIND WANDERING AND DAYDREAMING, ARE THEY DIFFERENT? includes mind wandering (Marchetti et al, 2014; but see Sugiura & Sugiura, 2020), and still others consider these distinct non-overlapping cognitive processes (Dorsch, 2015). For those who hold that there is a difference, daydreaming is defined as the deliberate and intentional shifting of attention away from the task or activity at hand (Klinger, 1978).…”
Section: Mind Wandering and Daydreaming Are They Different?mentioning
confidence: 99%
“…Is there a difference in what kinds of thoughts come to mind when they are intrusive (mind wandering) versus when they are intentionally accessed (daydreaming)? For example, several studies have suggested that daydreaming may lead to more positive affect and improve life satisfaction (Brenner et al, 2022;Sugiura & Sugiura, 2020). However, Killingsworth and Gilbert (2010) noted in a large-scale study involving several thousand participants that a wandering mind is an unhappy mind.…”
Section: Mind Wandering and Daydreaming Are They Different?mentioning
confidence: 99%
“…When people daydream, approximately 70% of these momentary thoughts are about other people (Song & Wang, 2012;Sugiura & Sugiura, 2020). In thinking about others, people make inferences about what they think or feel or how they may behave (Dennett, 1990).…”
Section: Simulation Changes the Selfmentioning
confidence: 99%